Determinants of the intention to seek psychotherapeutic consultation at work - a cross-sectional study in Germany - Fiona Kohl; Peter Angerer; Jeannette Weber (BMC, 2023)
Abstract Background Psychotherapeutic consultation at work (PT-A) provides employees with mental illnesses or subclinical symptoms a short-term and low-threshold access to psychotherapeutic care. However, practical experience shows that the utilisation rate seems low compared to expected demand. Therefore, this study aimed to identify determinants of utilisation by exploring associations between sociodemographic characteristics, psychological well-being, stigma-related barriers and psychosocial safety climate and the intention to seek PT-A. Methods Within a cross-sectional study, 658 participants were recruited via various social media channels in Germany. Participants answered an online questionnaire on potential determinants of (1) intention to seek PT-A in general and of intention to seek PT-A to specifically discuss (2) occupational burden and (3) private burden. Multiple ordinal regression analyses were conducted for the whole study sample and for the subgroups of participants screened positive and negative for current depression. Results Lower stigma-related barriers were associated with higher general intention to seek PT-A among all study groups. Lower psychological well-being was associated with higher general intention to seek PT-A and with higher intention to seek PT-A to discuss occupational and private burden, but only so in the subgroup of employees who were screened negative for current depression. Treatment experience was associated with higher intention to seek PT-A for occupational burden among participants screened negative but not among participants screened positive for current depression. No associations were found between age, gender, education or psychosocial safety climate and any variable of intention to seek PT-A. Conclusion Those results give an overview on potential determinants for the intention to seek PT-A, but future research with longitudinal designs is needed to confirm that those factors also determine actual utilisation of PT-A. Based on the results, practical implications might include antistigma campaigns and promotion of PT-A adapted to the aims of the consultation.